سير الولادة المهبلية والتخدير فوق الجافية - الدالي, عصام; عبد الرحمن, أحمد; الحريري, عدنان (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم التوليد وأمراض النساء - مشفى الأسد الجامعي – اللاذقية –سوريا. وامتدت من تاريخ 1/1/2004 وحتى 1/1/2005 وضمت 50 ماخضا خروسا بين عمر 16 – 35 بنسبة وكانت نتائج الدراسة على النحو التالي : النسبة الأعلى للمواخض الخروسات في الدراسة ضمن الفئة العمرية(21-25) سنة40%. كانت النسبة العظمى للمواخض الخروسات اللواتي أجري لهن تخدير فوق الجافية باتساع عنق رحم 4-6 سم (70% ). أعلى نسبة للمواخض الخروسات حسب العمر الحملي بين 38-40 أسبوعا حمليا ( 76% ). انتهت النسبة العظمى من الولادة بالطريق الطبيعي ( المهبلي ) بنسبة 94%. كانت النسبة الأعلى لدرجة الأ لم حسب المقياس الشفهي البسيط قبل تطبيق التخدير فوق الجافية الدرجة IV (70%) وبعد تطبيق التخدير أصبحت الدرجة I هي الغالبة(90%). ضمت الدرجة V لمقياس الألم حسب المقياس السلوكي للأ لم أعلى نسبة من المواخض(76%) بينما شملت الدرجةI النسبة الأعلى بعد التخدير (88%). كانت أعلى نسبة تسكين في الطور الثالث للمخاض(96%) ظهر تأثير للتخدير فوق الجافية على التقلصات الرحمية فقد تباطأ تواترها وقصرت مدتها الزمنية في (50%) من المواخض في الطور الأول وفي (40%) في الطور الثاني. كان أبغار النسبة العظمى من الولدان (7-10) في الدقيقة الأولى(82%) وفي الدقيقة الخامسة(98%). تحركت معظم الولادات خلال الساعات الأربع بعد الولادة(88%). حدث احتباس بولي لدى نفساء واحدة فقط. حدث صداع لدى نفساء واحدة فقط. ظهر انخفاض الضغط الشرياني في (6%) من المواخض. أبدت معظم المريضات ارتياحاً وتقبلا للتخدير فوق الجافية. This study was performed in Department of Obstetrics and Gynecology– AL- Assad University Hospital – Lattakia – Syria – in the interval between -01/01/2004- and till 01/01/2005 . It included 50 nulliparity parturient women between 15-35 years old . the results were as following: - The highest percentage of nulliparity parturient in the study was in the age group (21-35 ) years 40% . - Epidural anesthesia was applied to nulliparity parturients with uterine dilation of (4-6cm) in most cases (70% ). - The highest percentage of nulliparity parturients according to gestational age was between 38-40 gestational weeks ( 76% ). - Most deliveries ended in the normal vaginal delivery with percentage of ( 94% ) . - The highest percentage of the pain degree according to the simple oral scale before epidural anesthesia application was degree IV (70% ) and after its application the degree I became the most prevalent ( 90% ) . - Degree V of pain scale according to the behavioural scale of pain included the highest percentage of parturients ( 76% ) whereas degree I included the highest percentage after anesthesia ( 88% ) . - The highest percentage of painreliving was in the third phase of labor ( 96% ). - Epidural anesthesia has an effect on uterine contraction as its frequency slowed down and its duration became shorter in (50% ) of parturient in the first stage and in (40%) in the second stage . - Apgar of the highest percentage of newborns was ( 7-10 ) in the first minute (82%) and fifth minute ( 98% ) . - Most of puerperes moved during the first four hours postpartum ( 88 % ) . - Urinary retention occurred in one puerpera only . - One puerpera only had headacke . - Hyptentension occurred in ( 6 % ) of parturients . - Most patients showed good relief and acceptance to the epidural anesthesia .